2003
DOI: 10.1161/01.cir.0000080915.35024.a9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Perfusion Measurements for the Noninvasive Detection of Coronary Artery Disease

Abstract: Background-With MRI, an index of myocardial perfusion reserve (MPRI) can be determined. We assessed the value of this technique for the noninvasive detection of coronary artery disease (CAD) in patients with suspected CAD. Methods and Results-Eighty-four patients referred for a primary diagnostic coronary angiography were examined with a 1.5 T MRI tomograph (Philips-ACS). For each heartbeat, 5 slices were acquired during the first pass of 0.025 mmol gadolinium-diethylenetriamine pentaacetic acid/kg body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
388
1
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(412 citation statements)
references
References 30 publications
13
388
1
10
Order By: Relevance
“…Even though these data show a correlation between degree of ischemia and outcome [7], and provide a threshold for the appropriateness of revascularization, it is impossible to determine the clinical significance of reduced blood flow for an individual patient [8]. While generating fully quantitative data (i.e.…”
Section: Potential Applications Of Cardiac Hypoxia Imagingmentioning
confidence: 99%
“…Even though these data show a correlation between degree of ischemia and outcome [7], and provide a threshold for the appropriateness of revascularization, it is impossible to determine the clinical significance of reduced blood flow for an individual patient [8]. While generating fully quantitative data (i.e.…”
Section: Potential Applications Of Cardiac Hypoxia Imagingmentioning
confidence: 99%
“…There are convincing data that correlate MR indexes of perfusion with tissue perfusion in animal models 60,61 and excellent correlations with radionuclide imaging and invasive x-ray angiography in humans. [62][63][64] However, the published data so far do not demonstrate the feasibility of stress perfusion MR for everyday clinical use. The current studies are limited in that they were either retrospective (for patient enrollment and data analysis), required central venous catheters, imaged only 1 to 2 slices per heartbeat, or excluded patients with diabetes.…”
Section: Fuster and Kimmentioning
confidence: 99%
“…Recent advances in cardiac magnetic resonance imaging (cardiac MRI: CMR) have enabled dynamic first-pass contrast-enhanced imaging of the entire left-ventricular myocardium and cardiac wall motion imaging with improved image quality. Against this background, reports on the evaluation of coronary artery disease (CAD) and prognosis of patients suspected of having CAD by CMR have been increasing [1][2][3][4]. Recently, several prognostic studies with various follow-up periods using CMR have been reported [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%